2019
DOI: 10.14709/barbj.12.1.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Bats from the understorey of lowland tropical rainforests across Peninsular Malaysia

Abstract: To date, 110 bat species are recorded in Peninsular Malaysia. Many of these species depend upon tropical forests, which have rapidly decreased in extent over recent decades. Yet, updated information on species distributions in the region is still lacking. Here, we report bat species records and their distribution based from surveys undertaken at 30 lowland tropical rainforest sites across Peninsular Malaysia. We recorded 56 species from seven families. The three most abundant species across the peninsula were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The intermediate horseshoe bat Horsfield, 1823, Rhinolophus affinis, is one of the most abundant and widely distributed insectivorous bat species in South and Southeast Asia (Ith et al, 2016;Lim et al, 2019;William-Dee et al, 2019). Despite it is typically a forest species inhabiting primary and secondary forests (Kingston et al, 2006;Lim et al, 2019), studies have reported their availability in various habitat types, including cultivated habitats, degraded areas, farmlands and even in urban ones (Lim et al, 2019;Sia et al, 2015;William-Dee et al, 2019). Yet, there is data paucity on the diet of R. affinis in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate horseshoe bat Horsfield, 1823, Rhinolophus affinis, is one of the most abundant and widely distributed insectivorous bat species in South and Southeast Asia (Ith et al, 2016;Lim et al, 2019;William-Dee et al, 2019). Despite it is typically a forest species inhabiting primary and secondary forests (Kingston et al, 2006;Lim et al, 2019), studies have reported their availability in various habitat types, including cultivated habitats, degraded areas, farmlands and even in urban ones (Lim et al, 2019;Sia et al, 2015;William-Dee et al, 2019). Yet, there is data paucity on the diet of R. affinis in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%